2012
DOI: 10.1097/mph.0b013e318249a4be
|View full text |Cite
|
Sign up to set email alerts
|

Deferasirox Therapy in Children With Fanconi Aplastic Anemia

Abstract: Thirty-nine children with Fanconi aplastic anemia (FAA) have been followed up in our center between January 2008 and November 2010. Eight of these children (20%) with a transfusional iron overload had been undergoing deferasirox treatment during the study period. In the English literature, transfusional iron overload and the use of an iron chelator in children with FAA has not yet been evaluated. Here, we have presented the effectivity and tolerability of deferasirox in children with FAA and a transfusional ir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 5 publications
0
8
0
Order By: Relevance
“…Systematic studies of in vivo iron metabolism in patients with FA are currently lacking to the best of our knowledge; nevertheless, some recent reports found iron overload and excess serum ferritin levels. Elucidating iron metabolism in patients with FA requires investigations that might shed light in FA pathogenesis, while suggesting the prospect use of iron chelators in FA clinical management . Interestingly, transcripts for metallothioneins (2A and 3) were up‐regulated (Table ), consistently with the established link between oxidative stress and increase in metallothionein expression .…”
Section: Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“…Systematic studies of in vivo iron metabolism in patients with FA are currently lacking to the best of our knowledge; nevertheless, some recent reports found iron overload and excess serum ferritin levels. Elucidating iron metabolism in patients with FA requires investigations that might shed light in FA pathogenesis, while suggesting the prospect use of iron chelators in FA clinical management . Interestingly, transcripts for metallothioneins (2A and 3) were up‐regulated (Table ), consistently with the established link between oxidative stress and increase in metallothionein expression .…”
Section: Discussionmentioning
confidence: 76%
“…It has been reported that FA cells display hypersensitivity towards iron . Systematic studies of in vivo iron metabolism in patients with FA are currently lacking to the best of our knowledge; nevertheless, some recent reports found iron overload and excess serum ferritin levels. Elucidating iron metabolism in patients with FA requires investigations that might shed light in FA pathogenesis, while suggesting the prospect use of iron chelators in FA clinical management .…”
Section: Discussionmentioning
confidence: 99%
“…37,38,40,[60][61][62][63][64][65][66][67][68][69][70][71][72] Among 72 patients with β-thalassaemia major or intermedia who were treated with 20 mg/kg per day of deferasirox for 17 months, an increase in sCr levels >33% above baseline was observed in 46 (64%) patients and deferasirox was discontinued in seven (11%) patients. 60 Serum cystatin C levels are a more sensitive indicator of changes in GFR than are sCr levels.…”
Section: Epidemiologymentioning
confidence: 99%
“…Proteinuria, which may be intermittent, has been reported in about 18% of patients, and may be more common in children with Fanconi anaemia, with a single small study of this population reporting an unexpectedly high proportion of these children developing proteinuria [Tunc et al 2012]. It is recommended that urinary protein be monitored in patients who develop renal impairment.…”
Section: Renalmentioning
confidence: 99%